2023
DOI: 10.1177/08862605221145723
|View full text |Cite
|
Sign up to set email alerts
|

From Looking for Reason to Finding Meaning: A Spiritual Journey of Recovery From Sexual Trauma

Abstract: The current study aims to describe a spiritual facet of recovery processes from sexual trauma, as manifested in the transformation from the frustration and despair of looking for reasons to the traumatic event(s) to the growth and prosperity of finding meaning. A phenomenological research was conducted, interviewing individuals with a variety of affiliations to spirituality and to trauma: female survivors who turned to spirituality as part of their recovery process ( n = 17), spiritually oriented therapists wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 38 publications
1
3
0
Order By: Relevance
“…By accepting the existence of a spiritual, eternal dimension, participants demonstrated how their perspective of the world changed; they attributed spiritual principles and ideas to every event and circumstance, and specifically to extreme, dramatic ones. This is in line with previous research, which showed that sexual trauma survivors tend to look for explanations in spirituality (Park, 2020), give spiritual meaning to the traumatic event (Eytan & Ronel, 2023), and redefine the trauma as part of God’s plan (Ahrens et al, 2010).…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…By accepting the existence of a spiritual, eternal dimension, participants demonstrated how their perspective of the world changed; they attributed spiritual principles and ideas to every event and circumstance, and specifically to extreme, dramatic ones. This is in line with previous research, which showed that sexual trauma survivors tend to look for explanations in spirituality (Park, 2020), give spiritual meaning to the traumatic event (Eytan & Ronel, 2023), and redefine the trauma as part of God’s plan (Ahrens et al, 2010).…”
Section: Discussionsupporting
confidence: 92%
“…This can be explained by the theory of Positive Victimology (Ronel, 2015), which described the recovery process from victimization as a journey on an axis of positive experiences, from victimization toward the ultimate positive experience, namely love. However, in Spiritual Victimology (Eytan & Ronel, 2023), this consuming love is more than an ultimate positive experience: it is attributed to the individual’s connection with the Higher Power. Love, or a beneficiary holistic connection, which includes connections to one’s self, to one’s environment, and to God, is one of the basic principles of the upcoming theory.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations